The Colonial Legacy in India: How Persistent Are the Effects of Historical Institutions? - Lakshmi Iyer; Coleson Weir (Institute of Labor Economics (IZA), 2024)
Using updated data, we analyze the long-run effects of two British colonial institutions established in India. Iyer (2010) showed that areas under direct colonial rule had fewer schools, health centers, and roads than areas under indirect colonial rule. Two decades later, we find that these differences have been eliminated. Banerjee and Iyer (2005) found lower agricultural investments and productivity in areas with landlord-based colonial land tenure systems. Our updated data finds that only some of these differences have been eliminated. We conclude that the impact of colonial institutions can eventually fade away under the influence of targeted policies.
Keywords: P14; N45; O12; O13; 330; historical institutions; colonial rule; land tenure; agriculture; public goods; India